Roundness evaluation of cold forged pin head. - Abdullah, Ahmad Baharuddin; Salit, Mohd Sapuan; Samad, Zahurin; Abdul Aziz, Nuraini (2012)
Roundness is one of the criteria taken into account in precision forging. It become critical as the part need to be assembled with others part. In-accuracy may affect the overall performance of the assembly. In this study roundness of a cold forged pin head was measured. Pin head is a circular feature that has been designed to ensure accurate mating between the blade and the propeller. From the result, it is found that the roundness error of the pin head is low and overall is within the acceptable limit.